The B.C. Conference on the Family - Friesen, John (Canadian Journal of Counselling and Psychotherapy, 2012)
A unique three phase model of public consultation and enquiry was undertaken by the Government of British Columbia in co-operation with the religious communities with the purpose of identifying those forces in society which enrich family life and those that are pulling the family apart. This article contains a short description of the public enquiry together with some of the findings and recommendations that relate to counselling in such areas as counselling in the schools, preparation for marriage, interpersonal relationship training, selection of helping professionals, accountability of helping professionals, parent-counsellor-teacher partnership, values clarification, family studies, preventative and information services, and the establishment of the B.C. Council on the Family.